2008
DOI: 10.1007/s00330-008-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of osteoid osteoma by laser thermocoagulation under computed tomography guidance in pediatric patients

Abstract: To evaluate the efficiency of laser thermocoagulation under computed tomography (CT) guidance in the treatment of osteoid osteoma within a strictly pediatric group. Twenty-five patients aged 4 to 17 years were treated under CT by laser thermocoagulation. The nidus measured on average 10.1 mm. Pain relief was the main item for evaluation of the effectiveness of our treatment. Follow-up ranged from 3 months to 61 months (mean, 26 months). Technical success was achieved in 100%. Thermocoagulation proved to be ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…Pain, however, may require treatment. Nowadays, radiologists are well able to destroy the osteoma site by radiofrequency ablation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pain, however, may require treatment. Nowadays, radiologists are well able to destroy the osteoma site by radiofrequency ablation [28].…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided percutaneous therapies including core drill excision [19], laser ablation [20], and radiofrequency ablation [21] can preserve the surrounding normal bone structure by avoiding extensive digging of the cortex to find out the OO nidus. While the lower invasiveness and smaller bone defect of these methods have the advantage of short hospitalization and convalescence periods, they are accompanied by a higher recurrence rate of 13.5% [18].…”
Section: Discussionmentioning
confidence: 99%
“…The optic fiber is so small that it can be introduced through an 18-gauge spinal needle. This results in a minimally invasive procedure so that patients are only hospitalized one night and are able to bear weight and resume activities immediately after hospitalization [72]. As reported in Aschero et al, laser thermocoagulation was initially effective in 96% of the treated children with osteoid osteoma and had a positive longterm effect in 92% of the patients [72].…”
Section: Osteoid Osteoma and Osteoblastomamentioning
confidence: 92%
“…This results in a minimally invasive procedure so that patients are only hospitalized one night and are able to bear weight and resume activities immediately after hospitalization [72]. As reported in Aschero et al, laser thermocoagulation was initially effective in 96% of the treated children with osteoid osteoma and had a positive longterm effect in 92% of the patients [72]. In another, larger study, Gangi et al reported a primary clinical success rate of 99% and a secondary clinical success rate of 93.8% (with six recurrences) with the same technique [67].…”
Section: Osteoid Osteoma and Osteoblastomamentioning
confidence: 99%